Maharashtra State BoardSSC (English Medium) 7th Standard
Advertisement Remove all ads

Solve: 2 × {25 × [(113 - 9) + (4 ÷ 2 × 13)]} - Mathematics

Sum

Solve: 2 × {25 × [(113 - 9) + (4 ÷ 2 × 13)]}

Advertisement Remove all ads

Solution

2 × {25 × [(113 - 9) + (4 ÷ 2 × 13)]}
= 2 × {25 × [104 + (4 ÷ 2 × 13)]}
= 2 × {25 × [104 + (2 × 13)]}
= 2 × {25 × [104 + 26]}
= 2 × {25 × 130}
= 2 × 3250
= 6500.

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×